Trifluoromethoxy- and Fluorobenzhydryl-Tuned Nickel Catalysts for Polyethylene Elastomers - Ming Liu; Min Sun; Yanping Ma; Yizhou Wang; Mingfeng Li; Wen-Hua Sun (Molecules, 2025)
A series of para-trifluoromethoxy-substituted and fluorobenzhydryl-functionalized 1,2-bis(imine)acenaphthene ligands: 1-[2,6-{(4-F-C6H4)2CH}2-4-F3COC6H2N]-2-(ArN)C2C10H6 (Ar = 2,6-Me2C6H3 L1, 2,6-Et2C6H3 L2, 2,6-iPr2C6H3 L3, 2,4,6-Me3C6H2 L4, 2,6-Et2-4-MeC6H2 L5), were synthesized and used to generate their corresponding nickel(II) bromide complexes (Ni1–Ni5). Elemental analysis, 19F NMR, and FT-IR spectroscopy were employed to characterize these five nickel complexes. Single-crystal X-ray diffraction of Ni2 and Ni4 confirmed distorted tetrahedral geometries. Upon activation with either EtAlCl2 (ethylaluminum dichloride) or EASC (ethyl aluminum sesquichloride), these complexes showed exceptional high activities (up to 22.0 × 106 g PE mol−1 (Ni) h−1) and remarkable thermal stability (4.82 × 106 g PE mol−1(Ni) h−1 at 80 °C) towards ethylene polymerization. The resulting polyethylenes are highly branched, with the type and extent of branches tunable by temperature, solvent, and co-catalyst choice. Moreover, these polymers demonstrated excellent tensile strength (σb up to 20.7 MPa) and elastic recovery (up to 58%), characteristic of thermoplastic elastomers (TPEs). These results highlight the dual role of trifluoromethoxy and fluorobenzhydryl groups in enhancing catalytic performance and polymer properties.